Christian nurture through the family life ministry in Baekseok church in Korea. - Sun Lae Kim ([Manila] : South East Asia Graduate School of Theology, 1985)
Korea in the twentieth century is in the wake of a rapidly changing civilization which is largely due to the impact of the industrial revolution that is sweeping the country, and its resultant social progress. The old agricultural society is shifting towards the modern age of technology. The Korean family is caught up in these changes. As a result, the moral and spiritual upbringing of the family is highly affected. Traditional family concepts are giving way to new family patterns.
In partial fulfillment of the requirements for the Degree Master of Theology
A thesis presented to the faculty, South East Asia Graduate School of Theology
Thesis (M.Theo)-South East Asia Graduate School of Theology